ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI TENAGA KERJA MELAKUKAN MIGRASI SIRKULER (Studi di Kota Malang) - Davin Marela SE (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
The Phenomenon of population movement towards the city center is a better choice for laborfrom outside the city in the hope of getting a better life. This indicates that there are gaps in developmentand income in various regions. Todaro (2003) states that in the development process employment is animportant aspect that needs attention through increasing the quantity and quality of labor. This studyfocuses on labors who practice circular migration with commuting and seasonal characteristics inMalang City. The Research location in Malang City is based on the existence of wage gap. The conditionin Malang City tells that the wages offered are lower than one in Malang Regency. Nonetheless laborsfrom Malang Regency keep doing the circular migration. The purpose of this study is to determine the effect of wages in the destination area,transportation costs, education, gender and age on the actions of labor carry on circular migration inMalang City. This study employs primary data collected through survey with questionnaire as theinstrument. Data was collected in January and February of 2019 which were analyzed by using binarylogistic regression. The result shows that wages in destination area and age have a significant positiveeffect on the actions of circular migration of labors. Meanwhile, the transportation costs, education andgender have no effect on the actions of circular migration labor. Based on the result, labors from MalangRegency tend to choose to be commuting migrants instead of seasonal and are affected by wage indestination area and age.Keywords: Labor, circular migration, commuting labor migration, seasonal labor migration